Introduction [In Out of the shadow of famine] - Ahmed, Raisuddin; Haggblade, Steven (International Food Policy Research Institute, 2000)
The transformation in Bangladesh from traditional agriculture to a dynamic and progressively commercial agrarian society is a fascinating process that should interest many developing countries. This change is occurring despite monumental constraints and an adverse natural environment, providing lessons not only for the contemporary leaders of Bangladesh but for actors all across the developing world. By helping shape this transformation, food policy, in Bangladesh and elsewhere, plays a crucial role in addressing complex issues of producer incentives, consumer welfare, and the long-term economic growth necessary to alleviate poverty.